Rectify - Season 3 Episode 1-6 - Gyllenhaal, Stephen; Trilling, Lawrence; Gierhart, Bill; Cady, Patrick; Young, Aden; Spencer, Abigail; Clemens, Adelaide (Just Entertainment, 2017)
Despite an odd, sometimes contradictory account of his role in Hanna's death, the plea deal has gone through, making Daniel Holden, once again, a convicted murderer. As Daniel copes with probation, Janet prepares for his looming banishment and Amantha tries to build a life around something other than her brother's innocence. Even DA Sondra Person harbors lingering doubts about Daniel's guilt until George Melton's corpse turns up, raising new and troubling questions about the night Hanna died. [www.amazon.com]
Keywords: Blu-Ray-Disc